Diseño de propuesta de mejora de procesos para la empresa Lanas De Colombia basado en las herramientas lean manufacturing (2024)
The fundamental purpose is to design a process improvement proposal for the LANAS OF COLOMBIA company, using Lean Manufacturing tools as a basis. Throughout the document, the relevance of the Lean Manufacturing methodology is highlighted in the constant search for the improvement of production processes, focusing on waste reduction, flow optimization and quality improvement in the organization.